Improvement of the Rice “Easy-to-Shatter” Trait via CRISPR/Cas9-Mediated Mutagenesis of the qSH1 Gene - Sheng, Xiabing; Sun, Zhizhong; Wang, Xuefeng; Tan, Yanning; Yu, Dong; Yuan, Guilong; Yuan, Dingyang; Duan, Meijuan (Frontiers in Plant Science, 2020)
“Easy-to-shatter” trait is a major cause of rice crop yield losses, emphasizing the economic value of developing elite rice cultivars with reduced seed shattering capable of achieving higher yields. In the present study, we describe the development of new indica rice lines that exhibit lower rates of seed shattering following the targeted CRISPR/Cas9-mediated editing of the qSH1 gene. We were able to identify qSH1 mutant T0 transgenic plants, with transgene-free homozygous mutants being obtained via segregation in the T1 generation. We then utilized two T2 transgene-free homozygous lines in order to assess the degree of seed shattering and major agronomic traits of these mutant lines and of wild-type rice plants (HR1128-WT). This approach revealed that qsh1 homozygous mutant lines exhibited significantly reduced seed shattering relative to HR1128-WT without any significant changes in other analyzed agronomic traits. We then used these mutant lines to develop new promising hybrid rice lines with intermediate seed shattering. Overall our results reveal that combining targeted gene editing via CRISPR/Cas9 with heterosis utilization approach can allow for the efficient development of novel promising hybrid rice cultivars that exhibit a intermediate of seed shattering, thereby ensuring better stability and improved rice yields.